Profil Resiliensi Mahasiswa Program Studi Bimbingan dan Konseling - Wahyudi, Amien (Fokus Konseling, 2019)
This study aims to determine the condition of resilience of students of the Ahmad Dahlan University Guidance and Counseling Study Program. This research is a type of quantitative research with descriptive methods. The instrument used in this study is a resilience scale. The resilience scale consists of 25 items that have gone through a series of trials and have the value of the moving item item validity from 0.45 to 0.70, with a reliability value of 0.773 which is included in the high reliability. Subjects in this study amounted to 105 students of the Ahmad Dahlan University Guidance and Counseling Study Program taken using purposive sampling technique. The findings of this study show that as many as 69 or 65% of students are in the high resilience category, 33 or 31% of students are in the medium category, and as many as 3 or 4% of students are in a low categorization. The results of this study are useful for lecturers, and college counselors as consideration for facilitating students in developing individual resilienceKey Word : Resilience and Guidance and Counseling